Creating an augmented reality orientation using learning and design theories. Issue 2 (7th February 2022) - Kannegiser, Samantha
Abstract: This study investigates the impact of an augmented reality library orientation on first-year undergraduate students' feelings of anxiety toward the library and confidence using the library. This paper also reviews the best practices and theoretical foundation used for designing an augmented reality library orientation. The specific goals of the orientation are to increase students' comfort and confidence with the library and librarians as measured by a pre- and post-orientation survey. After taking the orientation, students reported an increased belief in the librarians' desire to help them and an increased confidence in knowing how to use an academic library but reported no change in viewing the library as a welcoming place, feeling overwhelmed by the library, or levels of comfort asking for help.